Prevalence of burnout among health sciences students and determination of its associated factors. Issue 2 (7th February 2021) - Tlili, Mohamed Ayoub; Aouicha, Wiem; Sahli, Jihene; Testouri, Ameni; Hamoudi, Marwa; Mtiraoui, Ali; Ben Dhiab, Mohamed; Chelbi, Souad; Ajmi, Thouraya; Ben Rejeb, Mohamed; Mallouli, Manel
ABSTRACT: Burnout is a major issue among healthcare students and a public health issue in general. Indeed, the consequences of student burnout are as complex as other mental distress factors, such as those concerned with smoking and alcohol consumption, or an unhealthy lifestyle.  This study aimed to determine the prevalence of burnout among health sciences students and to determine its associated factors. This is a cross-sectional descriptive study conducted among 368 students of a Tunisian institution using the French validated version of the MBI-SS. The prevalence of burnout was 64.4%. The presence of a diagnosed health problem, a diagnosed mental disorder or sleep problems were associated with burnout. Students who live alone are significantly the most emotionally exhausted (p=0.010) and the most cynical (p=0.033). Students who had a low socio-economic level are significantly more cynical than those who had a medium or high socio-economic level (p=0.032). Performing leisure activities and practicing physical activities were associated with emotional exhaustion (p=0.007, p= 0.008, respectively).In our study, burnout is prevalent among Tunisian health sciences students. Many factors were found to be associated with this syndrome. These findings reinforce the need to establish early preventive strategies to encounter this problem and its consequent risks.